Hiperrealitas dan Tanda dalam Kolaborasi Genshin Impact-Pizza Hut Indonesia (2023) - Hernanto, Pramudya Ardhika (Universitas Komputer Indonesia, 2025)
The video game company Hoyoverse who developed Genshin Impact can be seen collaborating with Pizza Hut Indonesia in 2023. In the collaboration, Genshin Impact utilized the images of the characters it had on the collaboration products between the two companies. This research is conducted using library research on Jean Baudrillard's thoughts on signs and hyperreality. This research found that the utilization of character images as signs during the collaboration can be seen in the creation of the new clothes design for the 2 characters involved in the collaboration. The sign created new value for the products sold in the collaboration. The value can be seen still attached to the product, even when its use value is already depleted. The sign is then used in the utilization of hyperreality during the collaboration to push the consumer to buy the collaboration package and receive virtual goods as a distinction. The said hyperreality can also be seen utilized during the collaboration by the existence of the collaboration characters Cosplayers used to pull the consumer to spend money for the ticket and attend the collaboration opening ceremony.